CASE BASED REASONING IMPLEMENTATION FOR WEB BASED KNOWLEDGE MANAGEMENT SYSTEM OF INFAK AND SEDEKAH MANAGEMENT - Firdaus, Mgs Afriyan; Indah, Dwi Rosa; Wijaya, Firman (Jurnal Sistem Informasi, 2018)
Knowledge management and knowledge sharing activities in management of infak and sedekah need to be developed using a knowledge management system and utilize the technology and equity knowledge of managers as well as proper solution retrieval for cases in the field. In this research, Case Based Reasoning (CBR) with Nearest Neighbor algorithm is implemented to support problem and knowledge solution management based on retrieve, reuse, revise and retain approach to solution of infak and sedekah management problem. The result found that CBR application on knowledge management system based on web based infak and sedekah can support problem solution management based on retrieve, reuse, revise and retain approach to knowledge data, problems and solutions that exist in knowledge base for web based management of infak and sedekah. Keywords: knowledge management system, case based reasoning, nearest neighbor algorithm, infak and sedekah, web